Identification and in situ removal of an inhibitory intermediate to develop an efficient phytosterol bioconversion process using a cyclodextrin-resting cell system. Issue 40 (15th July 2021) - Wang, Da; Zhang, Jian; Cao, Dan-Dan; Wang, Xuedong; Wei, Dongzhi
Abstract : We identified an inhibitory intermediate, 4-ene-3-keto steroids, that limits the bioconversion rate and provided a solution based on resin adsorption for improving 9α-OH-AD production efficiency in a commercial-scale process. Abstract : A classically versatile steroid intermediate, 9α-hydroxyandrost-4-ene-3, 17-dione (9α-OH-AD), can be obtained by phytosterol (PS) bioconversion using Mycobacterium . In this study, a cyclodextrin-resting cell reaction system with a high concentration of PS (50 g L −1 ) was used to produce 9α-OH-AD. However, the inhibitory effect of metabolic intermediates is a key factor limiting production efficiency. After the separation and identification of a series of metabolic intermediates, it was found that 4-ene-3-keto steroids, which are the first metabolites of sterol side-chain degradation, accumulated at the beginning of the bioprocess and had a remarkable inhibitory effect on bioconversion. The bioconversion rate was greatly improved when 5 g L −1 of macroporous adsorbent resin D101 was added to the reaction system in the initial phase. A certain amount of resin acted as a reservoir to remove the inhibitory intermediate in situ and facilitated the bioconversion process, and the 9α-OH-AD space–time yield increased to 8.51 g L −1 d −1, which was 23.15% higher than that without resin addition (6.91 g L −1 d −1 ) after 72 h bioconversion. In summary, we identified an inhibitory intermediate that limits the bioconversion rate and provided a solution based on resin adsorption for improving 9α-OH-AD production efficiency in a commercial-scale process.